Courtesy Authorship Practices Among First and Senior Authors: Evaluation of Motivations, Gender Bias, and Inequities - Condron, Mary E; Kibbe, Melina R; Azarow, Kenneth S; Martin, Matthew J (Annals of surgery, 2021)
A courtesy author is an individual who has not met authorship criteria but is listed as an author. This practice is common and often seen as victimless. Because publications are used for funding and promotion decisions, it is critical to understand biases in this practice.OBJECTIVESA courtesy author is an individual who has not met authorship criteria but is listed as an author. This practice is common and often seen as victimless. Because publications are used for funding and promotion decisions, it is critical to understand biases in this practice.An anonymous survey was conducted from March to October 2020 of first and senior authors of publications from 2014 to 2015 in 8 surgical journals. Authors were surveyed about demographic data, practice setting, and courtesy author practices.METHODSAn anonymous survey was conducted from March to October 2020 of first and senior authors of publications from 2014 to 2015 in 8 surgical journals. Authors were surveyed about demographic data, practice setting, and courtesy author practices.Three hundred forty-one authors responded (16% response rate). 75% were from academic practice settings. 14% reported adding courtesy authors 5 or more times in the past year. Courtesy authors were more often male (80%, P = 0.023), older (75%), and of higher academic rank (65%) than first/senior authors. All author groups were >75% white. When a reason was reported, 46% added a courtesy author due to avoid retaliation; 64% to avoid awkwardness. 26% expected reciprocal authorship offers. 92% of respondents acknowledge understanding International Committee of Medical Journal Editors authorship criteria. Women were less common among those added from goodwill than those added from fear (P = 0.039.) When courtesy authors were of a lower rank than first/senior authors, they were nearly twice as likely to be female (P = 0.0056) or non-white (P = 0.0184.).RESULTSThree hundred forty-one authors responded (16% response rate). 75% were from academic practice settings. 14% reported adding courtesy authors 5 or more times in the past year. Courtesy authors were more often male (80%, P = 0.023), older (75%), and of higher academic rank (65%) than first/senior authors. All author groups were >75% white. When a reason was reported, 46% added a courtesy author due to avoid retaliation; 64% to avoid awkwardness. 26% expected reciprocal authorship offers. 92% of respondents acknowledge understanding International Committee of Medical Journal Editors authorship criteria. Women were less common among those added from goodwill than those added from fear (P = 0.039.) When courtesy authors were of a lower rank than first/senior authors, they were nearly twice as likely to be female (P = 0.0056) or non-white (P = 0.0184.).Courtesy authors were more often male, older, and higher rank than first/senior authors. Fear of career consequences was a major motivator for including courtesy authors. Understanding the motivations and pressures leading to courtesy authorship will help to correct this practice.CONCLUSIONCourtesy authors were more often male, older, and higher rank than first/senior authors. Fear of career consequences was a major motivator for including courtesy authors. Understanding the motivations and pressures leading to courtesy authorship will help to correct this practice.